PGE2 suppression of innate immunity during mucosal bacterial infection - Agard, Mallory; Asakrah, Saja; Morici, Lisa A. (Frontiers in Cellular and Infection Microbiology, 2013)
Prostaglandin E2 (PGE2) is an important lipid mediator in inflammatory and immune responses during acute and chronic infections. Upon stimulation by various proinflammatory stimuli such as lipopolysaccharide (LPS), interleukin (IL)-1β, and tumor necrosis factor (TNF)-α, PGE2 synthesis is upregulated by the expression of cyclooxygenases. Biologically active PGE2 is then able to signal through four primary receptors to elicit a response. PGE2 is a critical molecule that regulates the activation, maturation, migration, and cytokine secretion of several immune cells, particularly those involved in innate immunity such as macrophages, neutrophils, natural killer cells, and dendritic cells. Both Gram-negative and Gram-positive bacteria can induce PGE2 synthesis to regulate immune responses during bacterial pathogenesis. This review will focus on PGE2 in innate immunity and how bacterial pathogens influence PGE2 production during enteric and pulmonary infections. The conserved ability of many bacterial pathogens to promote PGE2 responses during infection suggests a common signaling mechanism to deter protective pro-inflammatory immune responses. Inhibition of PGE2 production and signaling during infection may represent a therapeutic alternative to treat bacterial infections. Further study of the immunosuppressive effects of PGE2 on innate immunity will lead to a better understanding of potential therapeutic targets within the PGE2 pathway.